2017
DOI: 10.1007/s10067-017-3922-0
|View full text |Cite
|
Sign up to set email alerts
|

Sodium valproate modulates immune response by alternative activation of monocyte-derived macrophages in systemic lupus erythematosus

Abstract: The anti-inflammatory role of macrophages in apoptotic cells (ACs) clearance is involved in Systemic Lupus Erythematosus (SLE) pathogenesis. The efferocytic capability of macrophages is altered by M1/M2 polarization. Histone deacetylase inhibitors (HDACi) are proposed to enhance the expansion of M2 macrophages. Sodium valproate (VPA) is an HDACi with different anti-inflammatory properties. Here, we aimed to investigate the effects of HDACi by VPA on the polarization of monocyte-derived macrophages (MDMs) and r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 42 publications
1
28
0
Order By: Relevance
“…Several molecules and pathways have been suggested to be associated with controlling polarization and inflammatory profiles of Mϕ. For example, using MDMs of normal subjects and SLE patients, Saeed et al found that epigenetic modification is partly responsible for the Mϕ polarization profile in SLE (225). Their data showed that sodium valproate, an histone deacetylase inhibitor, can potently induce the alternative activation of Mo-Mϕ ex vivo and inhibit the pro-inflammatory profile of these cells when stimulated by apoptotic cells in vitro (225).…”
Section: Mo and Mϕ In Autoimmune Diseasesmentioning
confidence: 99%
“…Several molecules and pathways have been suggested to be associated with controlling polarization and inflammatory profiles of Mϕ. For example, using MDMs of normal subjects and SLE patients, Saeed et al found that epigenetic modification is partly responsible for the Mϕ polarization profile in SLE (225). Their data showed that sodium valproate, an histone deacetylase inhibitor, can potently induce the alternative activation of Mo-Mϕ ex vivo and inhibit the pro-inflammatory profile of these cells when stimulated by apoptotic cells in vitro (225).…”
Section: Mo and Mϕ In Autoimmune Diseasesmentioning
confidence: 99%
“…This was accompanied by an increase in both IL-10 and TGF- β and reduced levels of IL-1 β and TNF- α . These phenotypic changes could be an adjuvant for the treatment of autoimmune diseases [76].…”
Section: Effects Of Valproic Acid On Cells Of the Innate Immune Rementioning
confidence: 99%
“…Autopsies of patients with atherosclerosis revealed that a large number of macrophages, lymphocytes and foam cells are found in the coronary plaque, and the ratio of macrophages and lymphocytes is largest in the rupture plaque (25). Macrophages are mainly divided into two different subtypes: M1 and M2, which are predominantly located in unstable plaques and stable plaque tissues, respectively (5,6). It has previously been reported that iNOS, TNF-α, il-1β, IL-6, IL-12 and CD86 are major markers of M1-type macrophages (27).…”
Section: Discussionmentioning
confidence: 99%
“…For example, in one previous study, autopsies of patients with atherosclerosis discovered the accumulation of a large number of macrophages, lymphocytes and foam cells in the coronary artery plaques (2). Macrophages are mainly divided into two different subtypes: M1-type macrophages are mainly found in unstable plaques, whereas M2-type macrophages are predominantly found in stable plaque tissue (5,6). During the development of the disease, various external factors affect macrophages, and depending on the M1/M2 polarization status, the corresponding inflammatory process is highly different (5,7).…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation